2019
DOI: 10.1021/acs.inorgchem.9b02668
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-hexalanthanide Complexes: A New Synthetic Strategy for Molecular Thermometric Probes

Abstract: Reactions in solvothermal or microwave-assisted conditions between a hexanuclear rare-earth entity ([Ln6] with Ln = Eu–Dy) and m-halogeno-benzoic acids lead to three series of isostructural complexes with respective chemical formulas [Ln6(μ3-OH)2(H2O)2(NO3)2(3-cb)14]·4CH3CN, [Ln6(μ3-OH)2(H2O)2(NO3)2(3-bb)14]·6CH3CN, and [Ln6(μ3-OH)2(H2O)2(NO3)2(3-ib)14]·6CH3CN, where 3-cb–, 3-bb–, and 3-ib– represent 3-chloro-, 3-bromo-, and 3-iodo-benzoate, respectively. These three series of compounds are almost isostructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…[54][55][56][57] There are, however,s ome remarkable exampleso fh omo-or heterometallic Ln-to-Ln ET studies taking place within discretem olecules. [35,48,[58][59][60][61][62][63][64][65][66] Most of them are conducted in solution,w ith polydentate ligandsi nt he presence of two different lanthanide ions. [67][68][69] In many of these systems, there is little-to-no control over the location of each Ln III in the molecular scaffold, which is mainly dictated by statisticals peciation.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57] There are, however,s ome remarkable exampleso fh omo-or heterometallic Ln-to-Ln ET studies taking place within discretem olecules. [35,48,[58][59][60][61][62][63][64][65][66] Most of them are conducted in solution,w ith polydentate ligandsi nt he presence of two different lanthanide ions. [67][68][69] In many of these systems, there is little-to-no control over the location of each Ln III in the molecular scaffold, which is mainly dictated by statisticals peciation.…”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear Ln 3+ clusters attract increasing attention, as a result of their intriguing geometrical features and interesting properties related to magnetic, quantum computing and luminescent applications. The reported Ln 3+ clusters mainly include trinuclear (Ln 3 , Ln = Gd, Tb, Dy, Ho), [16,17] tetranuclear (Ln 4 , Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb), [18][19][20][21][22][23][24][25][26][27] pentanuclear (Ln 5 , Ln = Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb), [25] hexanuclear (Ln 6 , Ln = Pr, Ce, Eu, Gd, Tb, Dy, Er and Y), [27][28][29][30] octagon (Ln 8 , Ln = Gd, Tb, Dy, Ho), [31] nine-nuclear (Ln 9 , Ln = Nd, Sm, Eu, Gd, Tb, Dy, Ho), [32][33][34] eleven-nuclear (Ln 11 , Ln = Gd, Tb, Dy), [35] dodecanuclear (Ln 12 , Ln = Eu, Gd, Tb, Dy), [32,[36][37][38] hexadecanuclear (Ln 16 , Ln = Gd, Dy) clusters. [39] The number of Ln nuclei in Ln 3+ clusters was often controlled by the preferred coordination geometry of ligands [32] and the reaction environments.…”
Section: Cluster Chemistry Of Group 3 and 4 Metalsmentioning
confidence: 99%
“…[ 109 ] Guillou and co‐workers reported that solvothermal or microwave‐assisted reactions between RE 6 clusters (RE = Eu‐Dy, Y) and m‐halogeno‐benzoic acids can lead to MOFs with formula [RE 6 (μ 3 ‐OH) 2 (H 2 O) 2 (NO 3 ) 2 (3‐L) 14 ] (L = 3‐chloro‐, 3‐bromo‐, and 3‐iodo‐benzoate). [ 28 ] RE cations located at each vertex of quasi‐planar hexagon formed by two almost‐perfect equilateral triangles. Detailed study of luminescent properties revealed that these MOFs own strong intermetallic energy transfers, placing them promising candidates for thermometric probes in solid or solution state.…”
Section: Mofs Based On Y and Lns (Group 3 Metals)mentioning
confidence: 99%
“…Recently, Calvez and coworkers reported a series of hexalanthanide clusters with m-halogenobenzoic acid ligands as solid molecular thermometric probes. 126 Shown in Fig. 25 is the structure of a hexa-Dy cluster 29, [Dy 6 (3-bb) 14 ] (3-bb = m-bromo-benzoic acid).…”
Section: Organic-inorganic Hybrid Clustersmentioning
confidence: 99%